The Effect of Financial Literacy and Business Capital on the Sustainability of Broiler Chicken Micro, Small, and Medium Enterprises (MSMEs) in Pasir Pengaraian, Rokan Hulu Regency - Zuffriadis Salam; Makmur Makmur; Ratna Dewi (International Journal of Economic and Tourism Research, 2026)
This study aims to analyze the effect of financial literacy and business capital on the sustainability of broiler chicken micro, small, and medium enterprises (MSMEs) in Pasir Pengaraian, Rokan Hulu Regency. The research employed a quantitative approach with an explanatory design. The population consisted of 63 broiler chicken MSME owners, all of whom were selected as respondents using a saturated sampling technique. Data were collected through questionnaires and analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, t-tests, and F-tests with the assistance of SPSS version 25. The findings indicate that financial literacy has a positive and significant effect on business sustainability, with a significance value of 0.000 and a t-value of 6.181. Business capital also has a positive and significant effect on business sustainability, with a significance value of 0.009 and a t-value of 2.697. Simultaneously, financial literacy and business capital significantly influence business sustainability, as indicated by an F-value of 111.684 and a significance value of 0.000. The coefficient of determination (Adjusted R²) shows that 78.1% of the variation in business sustainability can be explained by financial literacy and business capital, while the remaining 21.9% is influenced by other factors outside the model. These results suggest that improving financial literacy and ensuring adequate business capital are essential strategies for enhancing the sustainability of broiler chicken MSMEs in Pasir Pengaraian.